Investigating the Prognostic Value of Serum Albumin Levels in Patients Undergoing Hemodialysis: A Systematic Review and Meta-analysis - Jessica Adrya; Calvin Sasongko; Melvin Andrean; Muhammad Faishal Kartadinata; Aveline Maisie Theis; Syafira Ayudiah Syah Putri; A. Muh. Yasser Mukti; Felly Moelyadi; Srigita Varsha; Veriantara Satya Dhika (Fakultas Kedokteran Universitas Pelita Harapan, 2025)
Background: Hypoalbuminemia, characterized by low serum albumin levels, is frequently observed in patients undergoing hemodialysis and has been identified as a potential predictor of increased mortality risk. This systematic review aims to evaluate the relationship between hypoalbuminemia and mortality in hemodialysis patients, assessing the prognostic value of serum albumin levels as an indicator for patient outcomes. Methods: A comprehensive search was conducted in databases including PubMed, Europe PMC, and Scopus to identify relevant studies. Studies were included if they investigated the association between serum albumin levels and mortality outcomes in adult patients undergoing hemodialysis. Data extraction was performed independently by two reviewers, focusing on study characteristics, patient demographics, albumin levels, and mortality outcomes. Quality assessment of studies was conducted using the Newcastle-Ottawa Scale (NOS). Result: A total of eight studies, encompassing 45,178 hemodialysis patients with a mean age in the 50s, met the inclusion criteria. The studies had a combined male cohort of 22,501 individuals. The definition of hypoalbuminemia varied across studies, with cutoff values ranging from 3.0 to 3.9 g/dL. Follow-up durations spanned from as early as 3 months to a maximum of 6.1 years. The meta-analysis revealed a pooled hazard ratio (HR) of 1.08 (95% CI: 0.94–1.25), suggesting a non-significant association between hypoalbuminemia and increased mortality risk (P = 0.28). However, substantial heterogeneity was present (I² = 79%), indicating variability across studies. Conclusions: Hypoalbuminemia showed a non-significant association with mortality in hemodialysis patients, though variability across studies suggests further research is needed for clarity.